Vibration energy harvesting from an array of flexible stalks exposed to airflow: a theoretical study. (22nd February 2016) - Gardonio, P; Zilletti, M
Abstract: This paper investigates the vibration energy harvesting of a system formed by an array of identical artificial flexible stalks connected by equal axial springs. The stalks are excited in bending by the propagating eddies produced by a mixing layer airflow at the top end of the canopy. The energy harvesting is localised in one pivotal stalk, which is equipped with a harvester. The paper first contrasts the spectra of the energy harvested by this system and by a classical system, formed by an equal array of mechanically uncoupled beams, which are all equipped with harvesters. Since the proposed system forms a periodic structure, this analysis considers variations of the stiffness of the harvesting stalk and of the connecting springs, which may lead to natural frequencies veering and mode localisation effects. Finally, the paper presents a parametric study that highlights how the bending stiffness of the harvesting stalk, the axial stiffness of the connecting springs and the energy absorption coefficient of the harvester influence the energy extraction. The study shows that, particularly in presence of strongly correlated drag force excitations produced on the stalks by the airflow, the energy harvested with the proposed system with a single harvester is comparable to that of a more complex and more expensive system formed by a whole array of harvesters.